Factors influencing adoption of climate resilient paddy production practices in Andhra Pradesh, India - Waris, Amtul; Rao, N Sunder (ORYZA-An International Journal of Rice, 2020)
This paper examined the factors affecting adoption of climate resilient practices in paddy production using data collected from farmers of Andhra Pradesh during the year 2019. Majority of the farmers reported increase in temperature, unpredictability in weather, reduced duration of winter, uneven and irregular rainfall as the climatic change events. The practices being followed by farmers which fit the adaptation criteria were timely sowing and weeding, proper spacing and formation of soil bunds. The climate resilient practices most preferredand prioritized by paddy farmers were direct sown rice, drought tolerant varieties, weather forecast services, integrated nutrient management, growing of green manure crops followed by crop diversification, crop insurance,system of rice intensification (SRI) and use of leaf color chart. Market demand, assured irrigation, land fertility, and availability of finance were the major factors governing the decision to grow crops. The educational level of farmers exhibited significant and positive correlation with practices namely SRI, use of leaf color chart, crop insurance, weather forecast services and drought tolerant varieties. Analysis of factors influencing the adoption of climate resilient paddy production practices would help to promote and disseminate these practices toincrease the adoption rate and also aid in the framing of appropriate policies.